Barriers and facilitators for breastfeeding very preterm infants: management of mother's milk in neonatal units in england, france and italy. (7th June 2011) - Bonet, M; Blondel, B; Forcella, E; Cuttini, M; Agostino, R; Draper, E; Zeitlin, J
Abstract : Introduction: Breastfeeding rates for very preterm infants at discharge home vary between European regions. Procedures related to the management of mother's milk may contribute to these differences. Aim: To describe policies and practices related to breastfeeding in neonatal units with a focus on the management of mother's milk in three European regions. Methods: A qualitative study of four neonatal units in regions with different breastfeeding rates: Ile-de-France (low), Trent (medium) and Lazio (high). Face-to-face, semi-structured interviews were conducted with healthcare providers in 2010. Verbatim transcripts were analyzed using a theoretical framework derived from the published literature; this analysis focused on comments related to mother's milk. Results: The Ile-de-France region had the most complex practices related to the use of mother's fresh milk, management of human cytomegalovirus-seropositive mothers and bacteriology screening; In Lazio, practices varied by unit, while in Trent there were no specific practices for bacteriology screening or cytomegalovirus (CMV). Informants in all regions felt that the use of fresh milk facilitated breastfeeding because it made more mother's milk available to the infant and enhanced maternal motivation. Respondents in Trent and Lazio expressed concerns about the effects of pasteurization on the nutritional and immunological properties of breast milk. In Ile-de-France respondents were concerned about health risks associated with CMV and bacterial contamination. Conclusion: The assessment of the benefits and risks associated with use of fresh human milk for very preterm infants differs in European Neonatal Intensive Care Unit. Complex practices for managing mother's milk may constitute a barrier to breastfeeding.